HOW FLOW STATE OCCURS OF THAI PROFESSIONAL GOLFERS - Jittjang, Karn; Jittjang, Karn; Singnoy, Chatkamon; Srichannil, Chomphunut (Journal of Faculty of Physical Education, 2022)
This study explored the experience of Flow States in Thai Professional golfers. Golf is a sport well-known for its challenge and playability for all age groups. The research collected data via a semi-structured interview with 10 Thai professional golfers, consisting of 4 male and 6 female golfers. The data in this study was analyzed quantitatively by the Reflexive Thematic Analysis (RTA) method. The research found that the flow experiences of the golfers were generated from two primary categories: one’s ability to regulate emotions and thoughts and one’s goals and confidence. The factors that create flow experiences consist of the awareness of one’s thoughts and emotions, the ability to manage negative thoughts, clear and challenging goals, the ability to handle less-than- expected results, accomplished goals, positive encouragement from others, and skill practicing routine. The research result could be used in the attempt to develop the potential of Thai professional golfers and other Thai athletes to compete at the national level. The understanding gained from the research could be applied in creating a practicing routine and adopted during a real competition to help athletes achieve their best performance